Ethics in Teaching in Medical Institutions (Homoeopathy for All, 2024)
The quintessential teacher embodies  a spectrum of roles, extending well  beyond the confines of classroom  instructions. Such an educator not  only imparts academic knowledge  but also instils ethical principles  within students. Educators bear a  significant moral obligation to keep  parents informed about their children's  academic performances. Given  the high esteem the society holds  for teachers, it is incumbent upon  them to strive to meet these societal  expectations and vice versa.
Keywords: Ethics; Teaching; Medical institutions; Mentorship; Exemplary Educator; Students; Teacher-Student dynamics